Situating mHealth in the workplace: a coordination studies perspective - Wolff-Piggott, Brendon (Department of Information Systems, 2021)
A central assumption of extant mHealth literature is that the technology empowers health care staff and leads to increased efficiency in service delivery. This assumption foregrounds the transformative potential of mHealth and the active appropriation of the technology, but obscures how it integrates with existing workplace arrangements. To interrogate the limitations of this dominant assumption, this research examines how mHealth is coordinated in the workplace in practice, and the perceptions and experiences of health care staff of the place mHealth takes in their daily concerns. In this way the research reveals how existing workplace arrangements influence the way that mHealth operates in practice, and builds on extant research to clarify how this can shift responsibility for the success of the implementation onto those staff with the least recognition and security. An interpretive case study explores the coordination of mHealth in the workplace, and analyses unexpected outcomes to identify their implications for theory and practice. In order to highlight this phenomenon the research focussed on the experiences of the clinic staff who were responsible for mHealth implementation, but were not the end users and who did not receive direct benefits themselves. The analysis drew on coordination studies to identify social and artefact-based coordination mechanisms, as well as the significance of relationships in mHealth in the workplace, yielding robust evidence that social coordination mechanisms rather than the fitness for purpose of the specific technology shaped the coordination process. Issues arising from the specific setting also influenced coordination in important ways that were not predicted in the official training material. The research makes three theoretical contributions that advance understanding of mHealth in the workplace through abduction. First, it identifies two novel coordination mechanisms: role flexibility and covert routines. Second, through the novel concept of multiple accountability, it challenges one of the key integrative principles proposed in the coordination studies perspective, problematising it and proposing that relationships between health intermediaries and local communities are far more influential for the coordination of mHealth than extant theory has so far proposed. Third, it carries important implications for future mHealth (and, more broadly, technology coordination) scholarship, providing evidence that existing coordination mechanisms and relationships may be as influential as the transformative potential of the technology itself. The research also contributes to practice by enhancing understanding of how health intermediaries may be empowered to effectively employ mHealth in the workplace. In a context of policy and funding uncertainty, this research contributes to an emerging literature identifying the practical mHealth issues primary health care staff face in a resource-poor environment, interrogating approaches that fail to recognise these realities.